Interventions for Psychological Health of Stroke Caregivers: A Systematic Review - Panzeri, Anna; Rossi Ferrario, Silvia; Vidotto, Giulio (Frontiers in Psychology, 2019)
Background: The increasing number of stroke patients (SPs) requires informal caregivers to bear a high burden of responsibilities and heavy (di)stress. Moreover, these issues could lead to the development of serious psychological problems (e.g.: depressive and/or anxious) that in turn could give rise to poor health-related quality of life outcomes. However, although the value of psychological interventions has been widely recognized for SPs, the scientific literature lacks an updated synthesis of interventions addressing the psychological health of their caregivers. Aim: The aim of this review is to summarize the interventions for the psychological health of stroke caregivers and provide a resume of literature-based evidence of their efficacy. Method: A literature review from 2005 to date was conducted in three online databases: PubMed, Scopus, and Google Scholar. Eligibility criteria for studies were (A) English language, (B) caregivers and patients aged 18 years or above, (C) SP’s caregiver beneficiating of a specific intervention, and (D) outcome measures addressing depressive and/or anxiety symptomology, quality of life, well-being, or burden. Results: Across the selected 45 studies, substantial differences are observable in three main categories: (a) type of intervention (b) techniques, and (c) operators. Interventions’ advantages and results are discussed. Overall, studies using psychological techniques, such as cognitive-behavioral therapy, coping skill-training, and problem-solving therapy, showed their usefulness and efficacy in reducing the caregivers’ depressive and anxious symptoms, and burden. Interventions led by psychologists and tailored to meet caregivers’ specific needs showed more positive outcomes. Conclusion: This review underlines the usefulness of psychological interventions aimed at reducing the psychological burden, such as anxious and depressive symptomatology, of SPs’ informal caregivers. Hence, psychological interventions for caregivers should be integrated as part of the stroke rehabilitation process to improve informal caregivers’ and patients’ quality of life and well-being.